The Effect Of Brand Awareness And Halal Labels Moderated By Religiosity On The Purchase Decision Of Indonesian Halal Brand Cosmetics By Women In Jabodetabek - Khairani, Najma; Sriminarti, Nurul (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to examine how brand awareness and halal labels moderated by religiosity can influence the purchasing decisions of Indonesian halal cosmetic brands by women, especially in the Greater Jakarta area. This study uses a quantitative method with a survey approach, where data is collected through questionnaires distributed to respondents who use halal skincare products. The variables analyzed include brand awareness, halal labels, religiosity, and purchasing decisions, which are then processed using statistical methods to test direct and mediating relationships between variables in this study. The results show that the variables of Halal Label, Religiosity, Brand Awareness significantly influence the Purchase Decision of Halal Cosmetic Products, the Religiosity variable is the variable that has the most influence on Brand Awareness and Purchase Decisions because the value of this variable is the largest. Based on the research that has been conducted, it is recommended to pay more attention to the religiosity of the market that will be the target of marketing and brands on halal cosmetics to convince buyers, so that consumers are confident in the purchasing decision of halal cosmetic products sold to the public, this is because the religiosity variable has a strong and moderating influence on brand awareness and purchasing decisions for halal cosmetic products with the highest value of 56% influencing brand awareness and purchasing decisions for halal cosmetic products